2012
DOI: 10.3109/14992027.2012.700772
|View full text |Cite
|
Sign up to set email alerts
|

Respect for a young male with and without a hearing aid: A reversal of the “hearing-aid effect” in medical and non-medical students?

Abstract: Findings were contrary to the "hearing-aid effect". Possible explanations are given and implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Individuals wearing the standard-sized BTE hearing aid were rated more trustworthy than individuals wearing a Bluetooth device. This finding may be consistent with Clucas et al (2012), where they found that the hearing aid users were rated as more "respectworthy," or it may indicate a negative view of individuals constantly having a Bluetooth device in their ear. Individuals using the earbud were rated as younger than their counterparts who had nothing visible in their ears (CIC condition).…”
Section: Discussionsupporting
confidence: 82%
“…Individuals wearing the standard-sized BTE hearing aid were rated more trustworthy than individuals wearing a Bluetooth device. This finding may be consistent with Clucas et al (2012), where they found that the hearing aid users were rated as more "respectworthy," or it may indicate a negative view of individuals constantly having a Bluetooth device in their ear. Individuals using the earbud were rated as younger than their counterparts who had nothing visible in their ears (CIC condition).…”
Section: Discussionsupporting
confidence: 82%